THE CONCEPT «SOUL/RUWX» IN ENGLISH AND KARAKALPAK PHRASEOLOGICAL AND PAREMIOLOGICAL UNITS (SCIENCE TIME JOURNAL, 2026)
The concept "Soul/Ruwx” in English and Karakalpak represents a complex and multifaceted dimension of human experience, often associated with emotions, identity, and spiritual essence. While inherently abstract, this concept is rendered tangible and comprehensible through the creative and evocative power of language. This study explores the conceptualization of "Soul/Ruwx" within English and Karakalpak phraseology, investigating how they shape and reflect cultural understandings of this fundamental human attribute.Drawing on the theoretical framework of Conceptual Metaphor Theory this research posits that abstract concepts like "Soul/Ruwx" are primarily understood through mappings onto more concrete domains of experience. By analyzing a carefully selected corpus of Karakalpak and English phraseological units and idiomatic expressions, this study aims to identify the prevalent conceptual metaphors that structure the understanding of "Soul/Ruwx" within these specific cultural contexts. By examining the linguistic encoding of "Soul/Ruwx", this research seeks to illuminate the cultural values, beliefs, and worldviews embedded within Karakalpak and English language and contribute to a deeper understanding of how abstract concepts are shaped and transmitted through linguistic expression.